Evaluation of the effect of head flexion and extension on the depth of orotracheal tube in children: Pediatric airway’s motion puzzle - Praveen Kumar; Kuldeep Singh; Akshat Gupta; Kundan Kumar (The Indian Anaesthetists' Forum)
Background: Endotracheal tube (ETT) placement in pediatric patients presents unique challenges due to anatomical differences such as a larger tongue, anteriorly placed larynx and narrower trachea. Correct ETT positioning is critical to prevent complications such as endobronchial intubation and desaturation. Previous studies have highlighted significant incidences of ETT malpositioning in pediatric populations undergoing anesthesia, necessitating precise investigation into the effects of neck movement on ETT placement. Aim: To assess the effects of head flexion and extension on ETT positioning in pediatric patients, specifically examining changes relative to the carina as the primary outcome, and vocal cords and incisor teeth as secondary outcomes. Setting and Design: This cross-sectional observational study was conducted in the Department of Anaesthesiology and Intensive Care of Maulana Azad Medical College and associated Lok Nayak Hospital, New Delhi. Materials and Methods: This observational study was conducted at a tertiary care center in North India over 12 months. Forty children aged 2–8 years, American Society of Anesthesiologists Grade I/II, undergoing elective surgery were included. Exclusion criteria comprised restricted head or neck movement, craniofacial abnormalities, and respiratory tract pathology. Patients were grouped by ETT size (internal diameter 4.5, 5, 5.5, and 6 mm). Measurements included changes in ETT-C distance, V-C distance (tracheal length), and I-V distance during neck flexion (80°) and extension (130°). Statistical analysis used paired Student’s t-tests (P < 0.05). Statistical Methods: Data were entered into an MS-Excel spreadsheet, and statistical analysis was performed using the Statistical Package for the Social Science (SPSS, version 26.0, IBM Corp., Armonk, NY, USA). Paired Student’s t-test was applied to check for statistical significance (set at P < 0.05 with 95% confidence intervals). Results: Significant variations were observed in the ETT-C distance with neck flexion (mean decrease, P < 0.01) and extension (mean increase, P < 0.01). Tracheal length decreased significantly with neck flexion (P < 0.01) but showed minimal change with extension (P = 0.58). The I–V distance varied significantly with both flexion and extension (P < 0.01), although subgroup analysis showed inconsistencies across ETT sizes. No postoperative complications were reported. Conclusion: The study highlights the significant impact of neck movement on ETT positioning in pediatric patients. While the tracheal length and I–V distance varied, ETT tip position was most affected, underscoring the need for careful monitoring and adjustment during anesthesia. These findings contribute valuable insights into pediatric airway dynamics, aiding clinicians in optimizing ETT placement to enhance patient safety.